Impactos regionales y sectoriales de la política monetaria en Colombia (2015)
This paper estimates the effect of monetary policy on economic activity in Colombia's regions and economy sectors, and evaluates the importance of the transmission channels. In order to achieve this goal, a distributed lag model is estimated combining regional and sectoral production data and using a measure of monetary policy shocks estimated in Quintero (2015a) with aggregate economy data. The main results show that there are sectoral differences in the impact of monetary policy on production. These differences in sectoral impacts, along with the differences in economic structure of departments, prove to be decisive in the regional transmission of monetary policy through the interest rate channel.